Dünya Ticaret Örgütü'nün tarım politikaları ve Türkiye'ye etkileri - Yılmaz, Hüner (My University, 2018)
ÖZETTarım sektörü, beslenme kaynağı olmasının yanı sıra ülke ekonomisine olan katkıları ile de oldukça önemli bir sektördür. Milli gelir, istihdam ve tarıma bağlı sanayi sektörüne yaptığı katkılardan dolayı stratejik bir sektör olan tarım sektörü, özellikle gelişmekte olan ülkelerde gelir kaynağı olması açısından payı oldukça büyüktür. Ülkelerin uygulamış oldukları tarife ve tarife dışı engeller tarım ticareti gelişimini engellemektedir. Tarım alanında uygulanan bu korumacı politikalar 1980’li yıllardan itibaren serbestleşmeye başlamıştır. Dünya Ticaret Örgütü öncesi dönemde tarım sektöründe çalışmalar yapılmış olsa da bağlayıcı kararlar alınamamıştır. Tarım sektöründeki kapsamlı çalışmalar Dünya Ticaret Örgütü’nün Uruguay Turu’nda ilk kez ele alınmış olup, 1995’te imzalanan Tarım Anlaşması ile tarım ticaretinin adil ve serbest bir şekilde dağılımı için pazara giriş, ihracat sübvansiyonları ve iç destekler ile ilgili düzenlemeler yapılmıştır. Çalışmada Dünya Ticaret Örgütü’nün tarım anlaşması ve akabinde uyguladığı politikalar sonrasındaki gelişmeleri ile Türkiye’deki tarım sektörüne etkileri ortaya konmuştur.

THE AGRICULTURAL POLICY OF WORLD TRADE ORGANIZATION AND ITS IMPACTS ON TURKEYThe agricultural sector is a very important sector not only because it is a source of nutrition but also because of its contribution to the country's economy. The agricultural sector, which is a strategic sector due to its contributions to the national income, employment and agriculture-related industrial sector, is quite large in terms of being a source of income, especially in developing countries. The tariffs and non-tariff barriers imposed by the countries impede the development of agricultural trade. These protective policies in the field of agriculture have been liberalized since the 1980s. Although studies were carried out in the agricultural sector before the World Trade Organization, no binding decisions were made. Comprehensive studies in the agricultural sector have been dealt with for the first time in the Uruguay Round of the World Trade Organization and the Agriculture Agreement signed in 1995 which made arrangements for access to market, export subsidies and domestic subsidies for the fair and free distribution of agricultural trade. In this thesis, World Trade Organization agreement on agriculture and the development after the policies applied with the effect of applied polices on the agricultural sector in Turkey have been revealed.
Keywords: Advanced Agricultural Negotiation; Agriculture; Agriculture Politics; Agriculture Trade; Dünya Ticaret Örgütü; Economic aspects; Economic development; Ekonomik gelişim; Ekonomik yönleri; İleri Tarım Müzakereleri; Korumacı Politikalar; Protection Politics; Subsidy; Sübvansiyon World Trade Organization; Tarım; Tarım Politikaları; Tarım Ticareti; Tarife; Tariff; Turkey; Türkiye; World Trade Organization